(untitled) (Research, Society and Development, 2021)
Marijuana is the most used illicit drug worldwide. The frequent use of marijuana in adolescence is very worrying, as it is associated with health problems. In Brazil, surveys on the use of psychotropic drugs with adolescent students were conducted in large cities. This study determined the prevalence and factors associated with marijuana use among adolescent students in the Brazilian city of Soure, Pará, in the Amazon region. In this cross-sectional study, 736 high school adolescent students provided information through a structured form at the three schools in Soure in November 2019. Marijuana use, in life and frequent (last 30 days), was calculated. Logistic regression models identified factors associated with different marijuana use. The rates of marijuana use in life and frequent were 17.7% and 7.1%, respectively. The behavioral pattern of the adolescents’ coexistence nucleus (parents, relatives, and friends) was fundamental for marijuana use in life. Also, the lack of interference or reduced participation of the family in the adolescent’s life, the inadequate family structure, and the continuous example of friends were associated with the frequent use of marijuana. Measures to control and prevent marijuana use are necessary and should be available to adolescents, their families, and friends in this remote area of the Amazon region.